Editor's Choice - External Validation of Models Predicting Survival After Ruptured Abdominal Aortic Aneurysm Repair. Issue 1 (January 2015) - van Beek, S.C.; Reimerink, J.J.; Vahl, A.C.; Wisselink, W.; Peters, R.J.G.; Legemate, D.A.; Balm, R.; ,
Abstract : Objective: Prediction of survival after intervention for ruptured abdominal aortic aneurysms (RAAA) may support case mix comparison and tailor the prognosis for patients and relatives. The objective of this study was to assess the performance of four prediction models: the updated Glasgow Aneurysm Score (GAS), the Vancouver scoring system, the Edinburgh Ruptured Aneurysm Score (ERAS), and the Hardman index. Design, materials, and methods: This was a retrospective cohort study in 449 patients in ten hospitals with a RAAA (intervention between 2004 and 2011). The primary endpoint was combined 30 day or in hospital death. The accuracy of the prediction models was assessed for discrimination (area under the curve [AUC]). An AUC >0.70 was considered sufficiently accurate. In studies with sufficiently accurate discrimination, correspondence between the predicted and observed outcomes (i.e. calibration) was recalculated. Results: The AUC of the updated GAS was 0.71 (95% confidence interval [CI] 0.66–0.76), of the Vancouver score was 0.72 (95% CI 0.67–0.77), and of the ERAS was 0.58 (95% CI 0.52–0.65). After recalibration, predictions by the updated GAS slightly overestimated the death rate, with a predicted death rate 60% versus observed death rate 54% (95% CI 44–64%). After recalibration, predictions by the Vancouver score considerably overestimated the death rate, with a predicted death rate 82% versus observed death rate 62% (95% CI 52–71%). Performance of the Hardman index could not be assessed on discrimination and calibration, because in 57% of patients electrocardiograms were missing. Conclusions: Concerning discrimination and calibration, the updated GAS most accurately predicted death after intervention for a RAAA. However, the updated GAS did not identify patients with a ≥95% predicted death rate, and therefore cannot reliably support the decision to withhold intervention.